2011
DOI: 10.1007/s11721-011-0054-z
|View full text |Cite
|
Sign up to set email alerts
|

Deciding on the wing: in-flight decision making and search space sampling in the red dwarf honeybee Apis florea

Abstract: During reproductive swarming and seasonal migration, a honeybee swarm needs to locate and move to a new, suitable nest site. While the nest-site selection process in cavity-nesting species such as the European honeybee Apis mellifera is very precise with the swarm carefully selecting a single site, open-nesting species, such as Apis florea, lack such precision. These differences in precision in the nest-site selection process are thought to arise from the differing nest-site requirements of open-and cavity-nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…[6]) is to give swarms a choice between two to six nest sites (but see [39] for a modelling study with a choice between 120 distinct nest sites). Natural honeybee swarms are likely to be faced with a greater number of potential nest sites to choose between.…”
Section: Simulations-the Possible Effects Of Scout Numbers On Decisiomentioning
confidence: 99%
“…[6]) is to give swarms a choice between two to six nest sites (but see [39] for a modelling study with a choice between 120 distinct nest sites). Natural honeybee swarms are likely to be faced with a greater number of potential nest sites to choose between.…”
Section: Simulations-the Possible Effects Of Scout Numbers On Decisiomentioning
confidence: 99%
“…Modelling studies have shown that such groups are able to compromise and head in a direction that is a middle ground between the two subgroups' locations (Leonard et al, 2012). Moving in the average direction also seems to be the tactic used by red dwarf honey bee (Apis florea) swarms, which often take to the air while still dancing for multiple locations (Oldroyd et al, 2008;Diwold et al, 2011;Makinson et al, 2011, and the giant honey bee Apis dorsata (Makinson, 2013). Both A. florea and A. dorsata build nests in the open and are rather tolerant with respect to where exactly they nest.…”
Section: Discussionmentioning
confidence: 99%
“…When selecting a nest site, it is essential the bees all arrive at the same site. Studies on nest-site selection in A. florea have suggested that due to A. florea's nest-site requirements (basically a shaded twig on a tree) and the abundance of potential nest sites, A. florea swarms only decide on the general direction they need to fly in to (Diwold et al, 2011;Makinson et al, 2011;Schaerf et al, 2011). Hence, the angular deviation in the dance will not necessarily negatively affect the ability of A. florea swarms to move cohesively to a new site (Diwold et al, 2011).…”
Section: Wwwfrontiersinorgmentioning
confidence: 99%
“…Studies on nest-site selection in A. florea have suggested that due to A. florea's nest-site requirements (basically a shaded twig on a tree) and the abundance of potential nest sites, A. florea swarms only decide on the general direction they need to fly in to (Diwold et al, 2011;Makinson et al, 2011;Schaerf et al, 2011). Hence, the angular deviation in the dance will not necessarily negatively affect the ability of A. florea swarms to move cohesively to a new site (Diwold et al, 2011). A. dorsata most likely uses visual cues to locate potential nest sites, as these bees prefer to nest in aggregations, mostly in trees that stand out in the environment or on conspicious buildings such as water towers or spires of temples (Oldroyd and Wongsiri, 2006).…”
Section: Wwwfrontiersinorgmentioning
confidence: 99%
See 1 more Smart Citation